Tell me who is your favorite politician, and i’ll tell you who you are: psychological factors of the ideal political leader’s image among Ukrainians - Kryvenko Iryna Stepanivna; Hrynyshyn Nataliya Oleksandrivna (Insight: the psychological dimensions of society, 2022)
The current situation in Ukrainian politics is resonant due to the polar public attitude to the top of power. Moreover, this attitude has a clear emotional component. Therefore, it is essential to understand the specifics of the ideal politician’s image for stabilizing the psychological climate in society. Purpose. The research aims to study the psychological qualities of voters in the context of their ideas about the perfect political leader. Methods. Based on the theories of identification with a political leader and the projection of personality traits on politicians, we conducted an empirical study to determine the hierarchical structure of the ideal political leader’s image (using a modified adjective test of politicians). We established the links of its components with the voters’ level of dispositional optimism, personal narcissism, and the intensity of the projection defensive mechanism. Results. We noted that the idea of a perfect politician in Ukrainian society characterizes him in terms of Machiavellianism, charisma, professionalism, and facade. The first aspect has the most significant loading in the factor structure and is especially important for the electorate with high narcissism. It indicates the desirability of a leader who will successfully solve problems and achieve the desired result. It confirms the theory of identification with the leader. The charisma of a leader becomes more important the higher the dispositional optimism of a person is. The high intensity of the projection as a defensive mechanism indicates some devaluation of the role of professionalism and facade and an emphasis on a politician’s charisma, which demonstrates ignoring of external, apparent signs of political leadership in favor of the desired features. Conclusions. The received results deepen the understanding of the psychological factors’ role in forming political preferences.